Advanced low grade serous ovarian cancer: A retrospective analysis of surgical and chemotherapeutic management in two high volume oncological centers - Di Lorenzo, Paolo; Conteduca, Vincenza; Scarpi, Emanuela; Adorni, Marco; Multinu, Francesco; Garbi, Annalisa; Betella, Ilaria; Grassi, Tommaso; Bianchi, Tommaso; Di Martino, Giampaolo; Amadori, Andrea; Maniglio, Paolo; et al. (Frontiers in Oncology, 2022)
Simple summary Low-grade serous ovarian cancer (LGSOC) represents an uncommon histotype of serous ovarian cancer (accounting for approximately 5% of all ovarian cancer) with a distinct behavior compared to its high-grade serous counterpart, characterized by a better prognosis and low response rate to chemotherapeutic agents. Similar to high-grade serous ovarian cancer, cytoreductive surgery is considered crucial for patient survival. This retrospective study aimed to analyze the outcomes of women affected by advanced stages (III–IV FIGO) of LGSOC from two high-volume oncological centers for ovarian neoplasm. In particular, we sought to evaluate the impact on survival outcomes of optimal cytoreductive surgery [i.e., residual disease (RD) <10 mm at the end of surgery]. The results of our work confirm the role of complete cytoreduction (i.e., no evidence of disease after surgery) in the survival of patients and even the positive prognostic role of a minimal RD (i.e., <10 mm), whenever complete cytoreduction cannot be achieved. Background Low-grade serous ovarian cancer (LGSOC) is a rare entity with different behavior compared to high-grade serous (HGSOC). Because of its general low chemosensitivity, complete cytoreductive surgery with no residual disease is crucial in advanced stage LGSOC. We evaluated the impact of optimal cytoreduction on survival outcome both at first diagnosis and at recurrence. Methods We retrospectively studied consecutive patients diagnosed with advanced LGSOCs who underwent cytoreductive surgery in two oncological centers from January 1994 to December 2018. Survival curves were estimated by the Kaplan–Meier method, and 95% confidence intervals (95% CI) were estimated using the Greenwood formula. Results A total of 92 patients were included (median age was 47 years, IQR 35–64). The median overall survival (OS) was 142.3 months in patients with no residual disease (RD), 86.4 months for RD 1–10 mm and 35.2 months for RD >10 mm (p = 0.002). Progression-free survival (PFS) was inversely related to RD after primary cytoreductive surgery (RD = 0 vs RD = 1–10 mm vs RD >10 mm, p = 0.002). On multivariate analysis, RD 1–10 mm (HR = 2.30, 95% CI 1.30–4.06, p = 0.004), RD >10 mm (HR = 3.89, 95% CI 1.92–7.88, p = 0.0004), FIGO stage IV (p = 0.001), and neoadjuvant chemotherapy (NACT) (p = 0.010) were independent predictors of PFS. RD >10 mm (HR = 3.13, 95% CI 1.52–6.46, p = 0.004), FIGO stage IV (p <0.0001) and NACT (p = 0.030) were significantly associated with a lower OS. Conclusions Optimal cytoreductive surgery improves survival outcomes in advanced stage LGSOCs. When complete debulking is impossible, a RD <10 mm confers better OS compared to an RD >10 mm in this setting of patients.